Teknologi, Data, Dan Layanan: Sinergi Digital Untuk Nasabah Pensiunan Di PT Bank Mandiri Taspen Kantor Cabang Kendari - Si Made Ngurah Purnaman; Andi Basru Wawo; Intihanah Intihanah; Nitri Mirosea; Fitriaman Fitriaman; Hasnidar Hasnidar; Erica Refor Beislin; Evania Renata Syalom; Melzi Farnatasya Putri (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This community service activity aims to improve the digital literacy of retired customers at PT Bank Mandiri Taspen Kendari Branch through educational socialization and direct mentoring related to digital banking services. The main problem identified was the limited digital understanding and skills of retired customers in using banking applications such as ANDAL by Taspen, ASABRI, and MOVIN, resulting in most customers still depending on face-to-face services. The methods used included educational socialization and direct practical mentoring conducted over three months at PT Bank Mandiri Taspen Kendari Branch within the framework of the Merdeka Belajar Kampus Merdeka (MBKM) program. The results showed an improvement in the understanding and confidence of retired customers in using digital banking services. Retired customers who previously relied entirely on face-to-face services began to demonstrate ability and independence in operating digital banking applications. The synergy between technology, data, and services realized through the Business Support role proved effective in supporting the optimization of digital services for retired customers. This activity makes a real contribution to improving the quality of banking services and strengthening the digital literacy of elderly groups in the banking environment.